MODERNISASI DALAM WAWASAN KEISLAMAN - Rofi?i, Abdul Halim (Jurnal Bestari, 1993)
Historically, the thinking of Islam has two patterns competing to progress each other. Firstly, the pattern of thinking traditionally is based on revelation. Secondly, one which is based on empirical thinking. European took the empirical thinking pattern after Moslem had left it. Consequently, the world of Islam has given chance to sophism thinking pattern to exist which emphasized transcendental life and ignored the development of material world. The experts of Islam studies think the fact has caused Islam to stagnate in education and culture.